The use of online information resources by nurses - Wozar, Jody A. (Medical Library Association, 2003)
Purpose: Based on the results of an informal needs assessment, the Usage of Online Information Resources by Nurses Project was designed to provide clinical nurses with accurate medical information at the point of care by introducing them to existing online library resources through instructional classes. Actual usage of the resources was then monitored for a set period of time. Methods: A two-hour hands-on class was developed for interested nurses. Participants were instructed in the content and use of several different online resources. A special Web page was designed for this project serving as an access point to the resources. Using a password system and WebTrends™ software, individual participant's usage of the resources was monitored for a thirty-day period following the class. At the end of the thirty days, usage results were tabulated, and participants were sent general evaluation forms. Results: Eight participants accessed the project page thirty-nine times in a thirty-day period. The most accessed resource was Primary Care Online (PCO), accessed thirty-three times. PCO was followed by MD Consult (17), Ovid (8), NLM resources (5), and electronic journals (1). The individual with the highest usage accessed the project page thirteen times. Conclusions: Practicing clinical nurses will use online medical information resources if they are first introduced to them and taught how to access and use them. Health sciences librarians can play an important role in providing instruction to this often overlooked population.